KUALITAS PELAYANAN IZIN MENDIRIKAN BANGUNAN (IMB) PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN POLEWALI MANDAR - Andi Muh. Alwi Yusuf; Munawir Arifin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2020)
The purpose of this research is to find out how the quality of building permit services in the investment service and integrated one door service of polewali mandar regency. The research method used is descriptive research with a qualitative approach. The results of this study are, a study of the quality of IMB services in Polewali Mandar district has increased in terms of ease of IMB services, although there are still found obstacles from the community regarding the maintenance of IMB, namely in the file requirements. The conclusion of this research is DPMPTSP in facilitating the community in taking care of the IMB, namely by having a website where to facilitate the public to obtain information about the IMB requirements and IMB management flow. The suggestion this research is DPMPTSP district of Polewali Mandar in order to maintain the quality of services related to IMB so that the community judges good and does not think less well of the services provided by DPMPTSP.